Community Based Cooperative melalui Pengembangan Desa Wisata Mangrove (Bakau Mangrove Center) Berbasis Edu Eco Wisata di Desa Banyu Urip, Ujung Pangkah, Gresik - Paramita Setyaningrum; Ahmad Hudaifah; Rizky Noviasri; Fandi Angga Prasetya; Irvan Adhin Cholilie (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Indonesia has many mangrove forest areas, including the Muara Gembong Bekasi Mangrove Forest, Karimun Jawa Mangrove Forest, Yogyakarta Kulon Progo Mangrove Forest, BJBR (Bee Jay Bakau Resort) Probolinggo. In some areas, many mangrove forests have been built, including the Wonorejo Mangrove Forest in Surabaya and Banyu Urip Mangrove Center (BMC) in Ujung Pangkah Gresik. Community service program will create a concept model for the development of the Mangrove Mangrove Center with a tourist area model approach and the concept of sustainable Eco Edu Wisata (sustainability development). In addition, the development of the BMC area will involve a lot of the community (Community Based Tourism). The goal to be achieved is to help develop BMC areas that are environmentally friendly, beneficial for education, and involve the role of the surrounding community. The proposed BMC Tourism Area development strategy is divided into several parts, namely the Infrastructure Development Plan, Introduction to the Development Plan, Tourists Enjoying the Nuance, Revisiting Tourists. The infrastructure development plan is divided into several activities, including: Development of Areas around Tourism, Development of Typical Products, Development of Attractions or Annual Events, Area Processing. The BMC area is known for its mangrove forests and Green Shell fishermen. Making the concept of a tourist area will make mangroves and Green Shells as BMC's advantages.